Debranching abdominal aortic hybrid surgery for aortic diseases involving the visceral arteries - Ma, Xiantao; Feng, Yi; Tardzenyuy, Mbenkum Achiri; Qin, Bo; Zhu, Qiangzhang; Akilu, Wajeehullahi; Li, Shiliang; Wei, Xiang; Feng, Xiang; Cheng, Cai (Frontiers in Cardiovascular Medicine, 2023)
Objective: Aortic diseases involving branches of the visceral arteries mainly include thoracoabdominal aortic aneurysm (TAAA), aortic dissection (AD) and abdominal aortic aneurysm (AAA). The focus of treatment is to reconstruct the splanchnic arteries and restore blood supply to the organs.This study retrospectively analyzed recorded data of patients at our institute and contrasted the outcomes with those of a similar group of patients who underwent conventional open repair surgery.Methods: Between 2019 and 2022, 72 patients underwent one-stage debranching abdominal aortic hybrid surgery. In all cases, we accomplished total visceral aortic debranching through a previous visceral artery retrograde revascularization with synthetic grafts (customized Y or four-bifurcated grafts), and aortic endovascular repair with one of two different commercially produced stent grafts . In some cases, we chose to connect the renal artery to the artificial vessel with a stent graft (Viabahn)and partly or totally anastomosed. We analyzed the results and compared the outcomes of the hybrid group with those of a similar group of 46 patients . These 46 patients, the conventional open group, were selected for having had thoracoabdominal aortic replacement between 2019 and 2022.Results: In the hybrid group, 72 visceral bypasses were completed, and endovascular repair was successful in all cases. No intraoperative deaths occurred. Perioperative mortality was 2.78%, and perioperative morbidity was 9.72%. At follow-up, there were unplanned reoperation rate of 4.29% and 5 (7.14%) deaths. In the conventional open group, 1 died intraoperatively，4 died perioperatively, perioperative mortality was 10.87%. At follow-up, 5 patients presented with synthetic grafts hematoma，4 patient died, and 6 patients required unplanned reoperation intervention. Conclusion: Hybrid surgery is technically feasible in selected cases for high-risk and high-age populations.